Identification of a thymidylate synthase gene within the genome of Chilo iridescent virus - Müller, Ann-Kristin; Tidona, Christian; Bahr, Udo; Darai, Gholamreza (Virus genes, 1998)
The thymidylate synthase (TS, EC 2.1.1.45) is essential for the de novo synthesis of dTMP in pro- and eucaryotic organisms. Consequently it plays a major role in the replication of the DNA genome of a cell or a DNA virus. The gene encoding the TS of Chilo iridescent virus (CIV) was identified by nucleotide sequence analysis of the viral genome and was mapped within the EcoRI CIV DNA fragments G and R. Computer assisted analysis of the DNA nucleotide sequence between the genome coordinates 0.482 and 0.489 revealed an open reading frame (ORF) of 885 nucleotides. This ORF was found to encode a polypeptide of 295 amino acid residues (33.9 kDa) that showed significant homologies to known TS of different species including mammals, plants, fungi, protozoa, bacteria, and DNA viruses. The highest amino acid homologies were found between the CIV-TS and the TS of herpesvirus ateles (54.0%), Saccharomyces cerevisiae (51.8%), herpesvirus saimiri (51.0%), rhesus monkey rhadinovirus (50.7%), mouse (50.5%), rat (50.2%), varicella-zoster virus (50.2%), equine herpesvirus 2 (50.0%), and the human TS (48.4%). The CIV-TS contains six amino acid domains that are highly conserved in the TS of other species. Within these domains the major amino acid residues are present for which a functional role has been reported. The CIV-TS was found to be more closely related to the TS of eucaryotes than to the TS of procaryotes indicating the phylogenetic origin of the CIV-TS gene. The identification of a TS gene in the genome of CIV is the first report of a viral TS that is not encoded by a herpesvirus or a bacteriophage.
Gesehen am 29.08.2024